2010
DOI: 10.1155/2010/719856
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Thioredoxin-Glutathione Reductase from LarvalTaenia crassiceps(Cysticerci)

Abstract: Mitochondrial thioredoxin-glutathione reductase was purified from larval Taenia crassiceps (cysticerci). The preparation showed NADPH-dependent reductase activity with either thioredoxin or GSSG, and was able to perform thiol/disulfide exchange reactions. At 25°C specific activities were 437 ± 27 mU mg−1 and 840 ± 49 mU mg−1 with thioredoxin and GSSG, respectively. Apparent Km values were 0.87 ± 0.04 μM, 41 ± 6 μM and 19 ± 10 μM for thioredoxin, GSSG and NADPH, respectively. Thioredoxin from eukaryotic sources… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 38 publications
2
15
0
Order By: Relevance
“…Recently, a similar behaviour was found also with thioredoxinglutathione reductase (TGR) isolated from the larval Taenia crassiceps (cysticerci) [10]. The cytosolic isoform of TGR shows a noticeably higher sensitivity to calcium ion inhibition in comparison to the corresponding mitochondrial isoform [10]. Taking into account the strict similarity between calcium and lanthanum ions, we have studied the effects of LaCl 3 on TrxR, in order to make a comparison with the results previously obtained on TrxR treated with calcium ions, especially considering the differential and contrasting inhibitory effects observed with this cation [1][2][3][4][5][6][7][8].…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…Recently, a similar behaviour was found also with thioredoxinglutathione reductase (TGR) isolated from the larval Taenia crassiceps (cysticerci) [10]. The cytosolic isoform of TGR shows a noticeably higher sensitivity to calcium ion inhibition in comparison to the corresponding mitochondrial isoform [10]. Taking into account the strict similarity between calcium and lanthanum ions, we have studied the effects of LaCl 3 on TrxR, in order to make a comparison with the results previously obtained on TrxR treated with calcium ions, especially considering the differential and contrasting inhibitory effects observed with this cation [1][2][3][4][5][6][7][8].…”
Section: Introductionsupporting
confidence: 55%
“…However, while the cytosolic isoform of this enzyme (TrxR1) is markedly inhibited by calcium ions, the corresponding mitochondrial enzyme (TrxR2) is far less affected [5]. Recently, a similar behaviour was found also with thioredoxinglutathione reductase (TGR) isolated from the larval Taenia crassiceps (cysticerci) [10]. The cytosolic isoform of TGR shows a noticeably higher sensitivity to calcium ion inhibition in comparison to the corresponding mitochondrial isoform [10].…”
Section: Introductionmentioning
confidence: 86%
“…As mammalian TrxRs, TGRs are selenoproteins with a C-terminal Gly-Cys-SeCys-Gly motif. The parasite TGR occurs in the cytosol and mitochondria of the worms (2,28,92). It is essential for Schistosoma survival and is currently investigated as a target for specific antischistosomal chemotherapy (137).…”
Section: The Gsh and Trx Systems Of Flatworms Are Linked By A Single mentioning
confidence: 99%
“…To date, TGR has been reported in the trematodes Schistosoma mansoni [26], Fasciola hepatica [27] and S. japonicum [28], as well as in the cestodes Echinococcus granulosus [29] and Taenia crassiceps [30]. Subsequent studies showed that in flatworms cytosolic and mitochondrial isoforms are encoded by a single gen [31] although with different kinetic properties [32].…”
Section: Introductionmentioning
confidence: 99%